Evaluation of Pomegranate Germplasm under Arid Condition (Indian Journal of Arid Horticulture, 2025)
Thirty-eight pomegranate genotypes were evaluated to assess the components of genetic variability with respect to growth, fruit yield, and quality traits. Considerable variability was observed in these characters. The number of fruits, fruit yield per plant, and fruit weight were observed to be highly heritable traits, which also showed a large magnitude of genetic advance. Thus, these characters should respond favorably to simple selection procedures in cultivar improvement attempts. Out of nine popular pomegranate varieties, Jalore Seedless, G-137, and Ganesh were observed to be superior with regard to fruit yield, while Mridula excelled in fruit quality, indicating promise for cultivation. However, all nine commercial types were prone to fruit cracking (30-90%). This study suggests systematic improvement in pomegranate not only for high-quality fruit yield but also for resistance to fruit cracking under hot arid environments.
Keywords: Arid environment; genetic variability; Pomegranate; Punica granatum